The ethics of information - Floridi, Luciano, 1964- (Oxford : Oxford University Press, 2013)
Ethics after the information revolution -- What is information ethics? -- The method of abstraction -- Information ethics as e-nvironmental ethics -- Information ethics and the foundationalist debate -- The intrinsic value of the infosphere -- The morality of artificial agents -- The constructionist values of homo poieticus -- Poiesis in the infosphere -- Artificial evil -- The tragedy of the good will -- The informational nature of selves -- The ontological interpretation of informational privacy -- Distributed morality -- Information business ethics -- Global information ethics -- In defence of information ethics.